1985
DOI: 10.1021/bi00348a044
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical characterization of the .alpha.-peptide of the sodium channel from rat brain

Abstract: The alpha-peptide of the rat brain sodium channel of apparent molecular weight 260K has been purified to homogeneity in order to determine its structural and chemical properties. By negative-stain electron microscopy, the molecule morphology of the solubilized channel protein appears as a stack of disks or rouleaux whose dimensions are 40 A X 200 A. Measurement of the secondary structure by circular dichroism shows that the alpha-peptide is a conformationally flexible polypeptide that contains mostly beta-shee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 47 publications
(49 reference statements)
0
24
0
Order By: Relevance
“…This step results in the loss of 40-60% of TTX-binding activity, as well as much of the purified protein (Talvenheimo et al, 1982;Weigele & Barchi, 1982;Rosenberg et al, 1984a;Elmer et al, 1985). The functional yields of sodium channel protein in all of these studies ranged from 3-12% of the initially extracted channel proteins (as measured with TTX binding) after reconstitution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This step results in the loss of 40-60% of TTX-binding activity, as well as much of the purified protein (Talvenheimo et al, 1982;Weigele & Barchi, 1982;Rosenberg et al, 1984a;Elmer et al, 1985). The functional yields of sodium channel protein in all of these studies ranged from 3-12% of the initially extracted channel proteins (as measured with TTX binding) after reconstitution.…”
Section: Discussionmentioning
confidence: 99%
“…Although these results suggest the necessity of this peptide for channel function, such experiments are subject to the criticism that any conditions used to disrupt intermolecular bonds between peptides might also disrupt vital intramolecular bonds on the large glycopeptide, thus denaturing it. Moreover, Elmer et al (1985) have recently reported isolating the large glycopeptide from rat brain in the absence of other subunits, while still retaining the ability of the protein to bind tetrodotoxin.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we examine sodium channel expression in astrocytes from developing rat optic nerve maintained in culture for up to 28 days with polyclonal antibody 7493, which was generated against purified rat brain sodium channel protein (Elmer et al, 1985). We demonstrate that sodium channels, as determined by 7493 immunoreactivity, are expressed by some astrocytes in culture for as long as 28 days, despite the absence of contact with neurons.…”
Section: Introductionmentioning
confidence: 90%
“…The expression of sodium channels in astrocytes cultured from PO and P7 rat optic nerves was examined immunocytochemically with polyclonal antibody 7493, which was generated against purified rat brain sodium channels (Elmer et al, 1985). This antibody immunoblots and immunoprecipitates from labeled membrane protein a 260 kDa polypeptide corresponding to the alpha subunit of the rat brain sodium channel, and has been shown to immunostain both the nodal axon membrane and astrocytes in situ (Black et al, 1989a,b).…”
Section: Astrocytes Exhibit Differential Sodium Channel Immunoreactivitymentioning
confidence: 99%
“…This distribution of channels will determine some of the differential electrical properties of one part versus another part of a given excitable cell. A number of laboratories have recently isolated and characterized the sodium channel protein as an extremely carbohydrate-rich polypeptide of Mr 260 kD (9,22,26,36). Although localization of important receptors and some morphological and electrophysiological evidence on sodium channel distribution has been described (4-6, 17, 20, 43, 57), little is known concerning the mechanisms that regulate and maintain their surface localization.…”
mentioning
confidence: 99%